KEBIASAAN MEMATIKAN LAMPU KETIKA TIDUR SEBAGAI IMPLEMENTASI HADIS DALAM KEHIDUPAN PONDOK PESANTREN AS-SUNNAH KOTA CIREBON - Siti Nur Amaliyah; Anisatun Muthi’ah; Ahmad Faqih Hasyim (IAIN Syekh Nurjati Cirebon, 2022)
Hadith is second Islamic sacred guidance after the Qur'an, so it has an important role in explaining the meaning of hadith which is applied in everyday life. The habit of turning off the lights when sleeping at the Islamic Boarding School is carried out after all student activities are completed, and is applied on the basis of the sunnah of the Prophet SAW, with the wisdom of carrying out this habit aiming to get benefit from Allah SWT. As for the implementation in order to gain understanding and benefits that can be obtained by yourself. As the formulation of the problem as follows: 1.) How do students and the entire community of As-Sunnah Islamic Boarding School understand the hadith of turning off the lights when sleeping, 2.) How do the people of As-Sunnah Islamic Boarding School get benefit by turning off the lights when sleeping. This research is a qualitative field research. The source of this research is the head of the madrasa, namely the caregivers of the As-Sunnah Islamic Boarding School in Cirebon City, the ustadz/ustadzah, and the students of the As-Sunnah Islamic Boarding School. The data collection technique was carried out using the interview method (in-depth interview) with the caregivers of the As-Sunnah Islamic Boarding School, ustadz, ustadzah, and the students. The method of observation when the implementation turns off the lights when sleeping is precisely by looking at the state of the room which then turns off the lights when going to sleep. The documentation method is in the form of supporting files. Data analysis uses data in the field, where the data obtained is in the form of conclusions or verification results from interviews and observations of the actual situation. The results of this study are the understanding of turning off the lights when sleeping for the people of the As-Sunnah Islamic Boarding School, seeing from the advice or orders of the Prophet SAW. Responding to lamps in ancient times with today's contexts are different so that the causes that allow the danger to be lost or less likely to occur, then this is sunnah, while the understanding according to the students themselves do not really understand the hadith, because the habit is only done when they are in the community. Pesantren and just starting to understand in terms of benefits only. The benefits of turning off the lights when sleeping for the As-Sunnah Islamic Boarding School itself are realizing a hadith and carrying out a sunnah, making sleep more sleepy, being able to rest the body optimally so that when you wake up you are refreshed, eye health is more awake, save electrical energy, and avoid unwanted things.